2016
DOI: 10.1186/s12936-016-1116-x
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs of fever to households in the middle belt of Ghana

Abstract: BackgroundMalaria is one of the main health problems in the sub-Saharan Africa accounting for approximately 198 million morbidity and close to 600,000 mortality cases. Households incur out-of-pocket expenditure for treatment and lose income as a result of not being able to work or care for family members. The main objective of this survey was to assess the economic cost of treating malaria and/or fever with the new ACT to households in the Kintampo districts of Ghana where a health and demographic surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 27 publications
(29 reference statements)
6
23
0
Order By: Relevance
“…The average indirect cost (GH¢25.04/US$6.59) was 1.7 times higher than the direct cost (GH¢14.87/US$3.91). This is consistent with many findings where the indirect costs of malaria treatment were higher than the direct costs of treatment [11,15,33,37,38]. Therefore, efforts to improve access to health care and reduction of financial burden to households in the treatment of malaria should not only be directed to direct medical costs but also indirect costs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The average indirect cost (GH¢25.04/US$6.59) was 1.7 times higher than the direct cost (GH¢14.87/US$3.91). This is consistent with many findings where the indirect costs of malaria treatment were higher than the direct costs of treatment [11,15,33,37,38]. Therefore, efforts to improve access to health care and reduction of financial burden to households in the treatment of malaria should not only be directed to direct medical costs but also indirect costs.…”
Section: Discussionsupporting
confidence: 89%
“…This study revealed that a large proportion of malaria patients treated with ACTs (66.9%) and a little more than 50% obtained the ACTs from formal health facilities (hospitals, Health centres, clinics and CHPS). High utilization of formal health facilities for malaria treatment has been reported in a previous studies[1115]. The high use of formal health facilities in our study could be attributed to NHIS as about 83% of patients were enrolled into the scheme.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…4 Licensed chemical shops are found in almost every town or village in Ghana and are the first point of call when most community members are unwell probably because of their ease of access to services at relatively lower cost. 5,6 They, therefore, play a complementary role in the formal health system by bringing health-care services to the doorsteps of people in deprived communities. 7 The Pharmacy Council of Ghana (PCG) oversees the registration, accreditation, and operations of LCS.…”
Section: Introductionmentioning
confidence: 99%